2011
DOI: 10.2903/j.efsa.2011.2264
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the substantiation of health claims related to soy isoflavones and protection of DNA, proteins and lipids from oxidative damage (ID 1286, 4245), maintenance of normal blood LDL cholesterol concentrations (ID 1135, 1704a, 3093a), reduction of vasomotor symptoms associated with menopause (ID 1654, 1704b, 2140, 3093b, 3154, 3590), maintenance of normal skin tonicity (ID 1704a), contribution to normal hair growth (ID 1704a, 4254), “cardiovascular health” (ID 3587), treatment of prostate c

Abstract: Scientific Opinion on the substantiation of health claims related to soy isoflavones and protection of DNA, proteins and lipids from oxidative damage (ID 1286, 4245), maintenance of normal blood LDL-cholesterol concentrations (ID 1135, 1704a, 3093a), reduction of vasomotor symptoms associated with menopause (ID 1654, 1704b, 2140, 3093b, 3154, 3590), maintenance of normal skin tonicity (ID 1704a), contribution to normal hair growth (ID 1704a, 4254), "cardiovascular health" (ID 3587), treatment of prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 116 publications
(206 reference statements)
0
1
0
Order By: Relevance
“…Other widely accepted products by consumers are erectile dysfunction (ED) supplements, which are featured in the online marketplace on pages with claims that they naturally treat ED. However, their efficacy and safety are largely unknown, which limits the ability to counsel patients regarding their use [37]. In a previous study, the authors identified 19 unique ingredients in testosterone-boosting supplements, and the literature review revealed 191 studies involving the 10 most frequent ingredients with different properties and efficacies.…”
Section: The Importance Of Food Safety and Food Quality In The Food Supplement Industrymentioning
confidence: 99%
“…Other widely accepted products by consumers are erectile dysfunction (ED) supplements, which are featured in the online marketplace on pages with claims that they naturally treat ED. However, their efficacy and safety are largely unknown, which limits the ability to counsel patients regarding their use [37]. In a previous study, the authors identified 19 unique ingredients in testosterone-boosting supplements, and the literature review revealed 191 studies involving the 10 most frequent ingredients with different properties and efficacies.…”
Section: The Importance Of Food Safety and Food Quality In The Food Supplement Industrymentioning
confidence: 99%